1824 Miss. Rev. Code 608 - (:unkn) unknown (My University, 1824)
Said president and selectmen may pass ordinances to regulate the keeping, carting and transporting gunpowder, or other combustible or dangerous materials, and, the use of lights in stables, to remove or prevent the construction of any fireplace, hearth or chimney, stoves, ovens, boilers, kettles or apparatus used in any house, building, manufactory or business which may be dangerous in causing or promoting fires; to appoint one or more officers, at reasonable times, to enter into and examine all dwelling houses, lots, yards and buildings, in order to discover whether any of them are in a dangerous state
Keywords: GUNPOWDER - STORAGE; GUNPOWDER - TRANSPORTATION